PENGARUH LABA BERSIH DAN ARUS KAS TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anita Rahayu; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTHigh returns are influenced by many factors including company profits, cash flows, internal conditions of the company and others. The purpose of this study is to find out and analyze how the effect of Net Profit and Cash Flow on Stock Returns on manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study is a type of explanatory research that empirically or quantitatively tests. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2018. The samples used in this study are 14 manufacturing companies listed on the Indonesia Stock Exchange for 3 years. The results of this study indicate that the R Square value of 0.388 shows that Stock Returns of 38.8% can be explained by Net Profit and Cash Flow, while the remaining 61.2% is explained by other variables not in the model or not examined. The conclusions in this study are the variables of Net Profit and Cash Flow have a simultaneous and partial significant effect on Stock Returns. While the dominant variable that influences Stock Return is Net Profit. Keywords: Net Profit, Cash Flow, Stock Return